Plant parasitic nematodes intercepted from imported ornamental plants - O.R. REDDY; RENU SHARMA, S. LATHA, D.V.N. BABU, N. SATHYANARAYANA (Indian Phytopathology, 2002)
The process and results of screening plant material for plant parasitic nematodes at the Plant Quarantine Station, Chennai, Tamil Nadu, India, are described. A total of 17 nematode spp., most of which are of economic importance, were intercepted onornamental plants during 1990-96. The significance of these species in terms of their pest status elsewhere in the world on crops important to India is discussed.